Design Of a Portal Website for One of The High Schools in Bandung - Cahyo Hermanto; Rahmat Anggit Wahyudi (LPPM STMIK Mardira Indonesia, 2024)
This study aims to create and construct a web gateway for a secondary school in Bandung. This website is anticipated to augment the engagement of students, parents, and school stakeholders in acquiring and disseminating information about school activities, student accomplishments, and diverse academic and extracurricular initiatives. The study technique encompasses user needs analysis, user interface (UI) design, and the development and execution of the website. The needs analysis approach entails interviews with school authorities, students, and parents to comprehend their expectations and prerequisites for the material that should be accessible on the portal. The outcome of this study is an online gateway that enables visitors to retrieve current information regarding class timetables, school notifications, event schedules, and students' scholastic accomplishments. In addition, the portal offers communication options that facilitate discussions and engagement between the school, students, and parents. This research is anticipated to benefit from enhancing communication and involvement among the school, students, and parents. Moreover, using information technology in education can enhance the efficiency and efficacy of the learning process at a high school in Bandung.